Economic Diversification of the Republic of Azerbaijan, the Role of the Middle Corridor as a Means to Decrease the Dependency of the Azerbaijani Economy on Oil Production - Guliyeva, Nazrin; Yagubov, Bahman; Ataliyeva-Rahimova, Gunay (ADA University, 2024)
The Middle Corridor project plays a crucial role at reconstruction of trade routes and enhancing the connection between two continents, Europe and Asia. It has particular importance to Azerbaijan in terms of economic diversification, economic growth, and political visibility especially in a period when instability, freight price increases, and lack of security is observed on the Russia’s Northern Corridor. This paper analyzes the problem of oil dependency of Azerbaijan’s economy, introduces policy alternatives to tackle the problem, and explores how implementation of the Middle Corridor project in Azerbaijan will contribute to the development of non-oil sector. By analyzing the political and socioeconomic impact that impede the implementation of the project, this paper examines the dire need for coordinated efforts to mitigate the effects of impediments with the purpose of achieving sustainable economic growth in the long-term.
Keywords: Azerbaijan -- Economic policy; Economic development -- Azerbaijan; Oil industry -- Economic aspects -- Azerbaijan; Middle Corridor (Eurasia); Transportation -- Economic aspects -- Azerbaijan; Public and International Affairs